1990
DOI: 10.1295/polymj.22.468
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis of Polyamides Containing Thymine Photodimer Units in the Main Chain and Application to Deep-UV Positive Type Photoresists

Abstract: ABSTRACT:Polyamides containing thymine photodimer units in the main chain were found to be applicable to a positive-chain scission type photoresist upon deep-UV exposure. Photo-dissociations of cyclobutane-type photodimers of thymine units caused the scission of the polymer chains, leading to decrease in molecular weight of the polymers. Photolithographic sensitivity and resolution test for these polymers indicated good sensitivity values with novel resolution of even 0.3 /lm. KEYWORDS Photodimerization / Thym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…For example, caged dimethylpiperidine can catalyze the cross-linking of poly­(hydroxyl amide) with bis­(activated esters) or bis­(vinyl sulfone) as a negative tone resist. Finally, polymers can also be cleaved directly with light or heat, , eliminating the need for additional reagents. For example, Ionov and co-worker have shown how temperature-dependent polymer solubility can be modulated by photocleavage reactions of o -nitrobenzyl esters, enabling patterning under mild and entirely aqueous conditions …”
Section: Clip Chemistry In Sacrificial Materials Designmentioning
confidence: 99%
“…For example, caged dimethylpiperidine can catalyze the cross-linking of poly­(hydroxyl amide) with bis­(activated esters) or bis­(vinyl sulfone) as a negative tone resist. Finally, polymers can also be cleaved directly with light or heat, , eliminating the need for additional reagents. For example, Ionov and co-worker have shown how temperature-dependent polymer solubility can be modulated by photocleavage reactions of o -nitrobenzyl esters, enabling patterning under mild and entirely aqueous conditions …”
Section: Clip Chemistry In Sacrificial Materials Designmentioning
confidence: 99%
“…34 Inaki and coworkers have extensively investigated the photocrosslinking of pendant thymine moieties on polymer chains for applications as reversible photo-resists. 11,[35][36][37] Warner and coworkers have reported the synthesis of thymine functionalized water soluble copolymers for photo-resist coatings. 38,39 Warner et al reported a new family of water-soluble photopolymers for their potential use as environmentally benign 'negative working' photoresists.…”
Section: Photo-resistsmentioning
confidence: 99%
“…118 In a similar manner to Chen et al, 118 Inaki et al prepared polyurethanes containing the thymine dimer as a site for photodegradation in a positive-type photo-resist. 121 Again however, Inaki found that the photo-cleavage reactions (performed using 249 nm UV light) were incomplete. 121 Obviously, this "dimer-rst" approach relies on the synthesis of large enough amounts of the cyclobutane compounds for synthetic incorporation into new monomer structures.…”
Section: Linear Polymers Containing Pre-synthesised Cyclobutane Segme...mentioning
confidence: 99%
See 1 more Smart Citation
“…We further investigated the photoreversibility of Thy‐P n BuA‐Thy polymers. The thymine dimers are generally capable of retro‐[2π + 2π] dimerization upon exposure to UV irradiation with wavelengths shorter than 250 nm . To study the retro‐[2π + 2π] photoreactions of the polymers, thin films were first photopolymerized (at 302 nm, 64 J cm −2 ).…”
Section: Characteristics Of Irradiated Thy‐pnbua‐thy Polymers (Gpc Data)mentioning
confidence: 99%